USA: Ophthalmologic Evaluation and Management of Acute Stevens-Johnson Syndrome - Gregory, Darren G. (Frontiers in Medicine, 2021)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) can cause significant damage to the ocular surface and eyelids. The sloughing and inflammation of the ocular mucosal epithelium during the acute phase may lead to scarring sequelae of the eyelids and ocular surface, resulting in pain and vision loss. Amniotic membrane transplantation (AMT) to the eyes and eyelids during the initial 1–2 weeks of the disease can decrease the chronic sequelae. The main development in the ophthalmologic treatment of SJS/TEN in the USA over the last 15 years has been the use of AMT on the ocular surface and eyelids during the acute phase. The evolution of AMT techniques, refinement of the evaluation of the eyes in acute SJS, and the efforts to increase the use of AMT in the USA are discussed.